Empowering Marginalized Children Through Educational Board Games: A Community-Based Approach to Literacy and Numeracy Development - Sandjaja, Meilani; Yuliawati, Livia; Eunike, Prisca; Ega Vishnu Christian, Yohanes; Shienny Davanca Lisvantoro, Stephanie; Priska Christian, Jennifer; Aishvarya Divani, Shri (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Foundational literacy and numeracy remain major educational challenges among marginalized children in Indonesia, particularly those from street-connected and low-income communities who have limited access to engaging learning resources and structured educational support. This community service project aimed to evaluate the effectiveness of the Kicara Board Game ("Kita Cerdas, Percaya Diri") as an innovative game-based learning medium for improving literacy, numeracy, and self-confidence among children at Kelompok Belajar Mengajar (KBM) Raja Petojo, Surabaya. The program employed a one-group pretest–posttest design complemented by qualitative reflection sessions ("Hutan Inspirasi") and was implemented through socialization, facilitator training, technology integration, mentoring, and evaluation over an eight-month period. Twenty participants, ranging from kindergarten to junior secondary level, were divided into a Main Group and a Star 2 Group. Learning outcomes were assessed using five-level ordinal categories for literacy, numeracy, and self-confidence before and after the intervention. The findings demonstrated substantial improvements in literacy, with all participants reaching the very high category at posttest, while numeracy outcomes also increased markedly, particularly among participants achieving high and very high performance levels. Improvements in self-confidence were evident but comparatively more modest, especially among younger learners. These findings indicate that game-based, community-centered learning interventions effectively strengthen foundational academic competencies, although affective development requires longer-term and family-supported mentoring. The study highlights the potential of educational board games as sustainable learning innovations for marginalized communities within non-formal education settings.Literasi dan numerasi dasar masih menjadi tantangan utama bagi anak-anak marjinal di Indonesia, khususnya mereka yang berasal dari komunitas anak jalanan dan keluarga berpenghasilan rendah yang memiliki keterbatasan akses terhadap media pembelajaran yang menarik dan dukungan pendidikan yang terstruktur. Program pengabdian kepada masyarakat ini bertujuan untuk mengevaluasi efektivitas Kicara Board Game ("Kita Cerdas, Percaya Diri") sebagai media pembelajaran berbasis permainan yang inovatif dalam meningkatkan kemampuan literasi, numerasi, dan kepercayaan diri anak-anak di Kelompok Belajar Mengajar (KBM) Raja Petojo, Surabaya. Program menggunakan desain one-group pretest–posttest yang dipadukan dengan sesi refleksi kualitatif ("Hutan Inspirasi") serta dilaksanakan melalui tahapan sosialisasi, pelatihan fasilitator, integrasi teknologi, pendampingan, dan evaluasi selama delapan bulan. Sebanyak 20 peserta, mulai dari jenjang taman kanak-kanak hingga sekolah menengah pertama, dibagi ke dalam Kelompok Utama dan Kelompok Bintang 2. Hasil pembelajaran dievaluasi menggunakan kategori ordinal lima tingkat pada aspek literasi, numerasi, dan kepercayaan diri sebelum dan sesudah intervensi. Hasil penelitian menunjukkan peningkatan yang signifikan pada kemampuan literasi, di mana seluruh peserta mencapai kategori sangat tinggi pada posttest. Kemampuan numerasi juga mengalami peningkatan yang nyata, terutama pada proporsi peserta yang mencapai kategori tinggi dan sangat tinggi. Sementara itu, kepercayaan diri menunjukkan peningkatan, meskipun relatif lebih moderat, khususnya pada peserta usia yang lebih muda. Temuan ini menunjukkan bahwa intervensi pembelajaran berbasis permainan yang berpusat pada komunitas efektif dalam memperkuat kompetensi akademik dasar, namun pengembangan aspek afektif memerlukan pendampingan yang lebih berkelanjutan serta dukungan keluarga. Penelitian ini menegaskan potensi board game edukatif sebagai inovasi pembelajaran yang berkelanjutan bagi komunitas marjinal dalam penyelenggaraan pendidikan nonformal.